The effect of career guidance on undergraduate medical students' specialty preferences - El Naggar, Marwa Ahmed; Mohamed, Rehab Ali; Almaeen, Abdulrahman Hamdan (Journal of the Pakistan Medical Association, 2021)
Abstract Objectives: To design and implement a career guidance program for medical students and evaluate its effectiveness. Methodology: A quasi-experimental single group design was applied in this ethically approved study at Jouf University, Sakaka, Saudi Arabia. A modified Medical Career Development Inventory (MCDI) covering 5 areas was utilized aimed at assessing how much students’ thinking or planning had improved after implementing the designed career guidance program. The study followed the widely used approach for curriculum development: Kern's 6 steps for course design. A comprehensive sample (n=82) taken from the Phase II (4th and 5th year) male (n=47) and female (n=35) students in the college of medicine during the academic year of 2018-2019. Results: Using focus group interview techniques on 50 students, we found that 27% requested lectures about career decision-making, 53% highlights about the Saudi Medical License Exam, 20% information on different specialties, 65% internal/external postgraduate programs, and 35% pros and cons of each specialty. The post-intervention results showed that the total MCDI scores increased (pre-test mean±SD of 2.60 ±0.29 versus post-test mean±SD of 3.16± 0.20, p: 0.018), suggesting an improved degree of vocational development. Conclusion: This study significantly improved career development levels among our students by assisting their readiness for career decision-making. Integrating career guidance in the formal curriculum is recommended. Continuous...